Large-Scale, Ultrasensitive, Highly Reproducible and Reusable Smart SERS Platform Based on PNIPAm-Grafted Gold Grating; ChemNanoMat; Vol. 3, iss. 2 - Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich; Kalachyova E. Evgeniya; Kolska Z. Zdenka; Libansky M. Milan; Zima I. Irzhi; Svorcik V. Vaclav; Lyutakov O. Oleksy (2017, 2017)
Title screen